Private Law in Eastern Europe Autonomous Developments or Legal Transplants? - Jessel-Holst, Christa; Kulms, Rainer (Mohr Siebeck, 2011)
More than 20 years have passed since the downfall of socialist systems. To accelerate transformation processes utmost priority was given to the recognition of property rights, an indispensable requirement for free market economies. Regulators soon came to realize that the success of transformation was conditioned on a more systematic approach towards codified civil law and business law. Numerous comparative law studies on individual Eastern European states have been undertaken, but they fail to portray the dynamic in its full scope. Studies adopting long-term perspectives and offering multi-nation comparisons are particularly rare. In March 2009, a symposium was held at the Hamburg Max Planck Institute for Comparative and International Law to address these shortcomings. In this conference volume Christa Jessel-Holst, Rainer Kulms, and Alexander Trunk assemble the contributions by international policy advisors and scholars from Eastern and South Eastern Europe (Bosnia and Herzegovina, Bulgaria, Croatia, Hungary, Poland, Romania, Russia, Serbia, Slovenia and Ukraine) assessing codification processes in classic civil law fields and company and capital market laws. In spite of comparable transformation problems, the individual processes are moving forward quite disparately, oscillating between 'old' socialist codifications, legislative projects faithful to the acquis communautaire and new codifications with a distinctly autonomous approach. Nonetheless, most transformation states are united in their effort to establish efficient court systems which can handle the acquis without being positivistic. Contributors: Jürgen Basedow, Rainer Kulms, Michel Nussbaumer, Frederique Dahan, Thomas Meyer, Alexander Komarov, Volodymyr Kossak, Jelena Perovi?, Camelia Toader, Verica Trstenjak, Christian Takoff, Tatjana Josipovi?, Meliha Povlaki?, Du?an Nikoli?, Mirko Vasiljevi?, Alexandra Makovskaya, Oleg Zaitsev, Ionu? Radule?u, Tania Bouzeva, Radu Catan?, András Kisfaludi, Krzysztof Oplustil, Arkadiusz Radwan